Trichoderma shapes phytophagous and entomophagous arthropod community in common bean fields - Pierluigi Forlano; Daniele Curcio; Raffaele Cavaliere; Stefania Mirela Mang; Enrica De Falco; Antonino Modafferi; Giulia Giunti (Crop Protection, 2026)

Lethal and sub-lethal effects of two botanical nano-insecticides against Liposcelis bostrychophila - Maria Pineda; Ilaria Latella; Pierluigi Forlano; Giulia Giunti; Orlando Campolo; Antonino Modafferi; Vincenzo Palmeri (Journal of Stored Products Research, 2026)

Metabolic and microbial responses of Ceratitis capitata to essential oil-based nano-emulsions: Implications for pest management - Antonino Modafferi; Alberto Urbaneja; Cristina M. Aure; Giulia Giunti; Isabel Martinez-Sañudo; Annamaria Ienco; Orlando Campolo; Vincenzo Palmeri; Meritxell Perez-Hedo (Pesticide Biochemistry and Physiology, 2025)

Green pest control strategies: essential oil-based nano-emulsions for Delottococcus aberiae management - Antonino Modafferi; Alberto Urbaneja; Cristina M. Aure; Francesca Laudani; Vincenzo Palmeri; Giulia Giunti; Orlando Campolo; Meritxell Pérez-Hedo (Journal of Pest Science, 2025)
Increasing restrictions on synthetic pesticides due to environmental and health concerns have driven the search for alternative environmentally friendly pest management strategies. Essential oils (EOs) from plants like garlic ( Allium sativum ), clove ( Syzygium aromaticum ), and eucalyptus ( Eucalyptus camaldulensis ) have shown promise as bioinsecticides. However, their volatility, low water solubility, and short persistence limit their practical application in Integrated Pest Management programs. To address these challenges, we developed nano-emulsions of these EOs using a high-pressure microfluidization technique, achieving stable formulations with nano-sized droplets (< 200 nm) and optimal polydispersity index and zeta potential values. The insecticidal efficacy of these EO-based nano-emulsions was tested against the invasive citrus pest Delottococcus aberiae , with garlic nano-emulsion (GNE) exhibiting the highest mortality (100% within 24 h), significantly outperforming clove and eucalyptus formulations. GNE exhibited a dose–response mortality against D. aberiae while demonstrating no toxicity (100% of survival) toward Cryptolaemus montrouzieri and no phytotoxicity on citrus plants. Moreover, gene expression analysis revealed that GNE application triggered the overexpression of key genes involved in plant defense pathways, including ICS2 , NPR1 , PAL , and MYC2 , suggesting the activation of both salicylic acid and jasmonic acid signaling pathways. This dual action—direct pest control and enhancement of plant defenses—positions GNE as a powerful tool in sustainable citrus pest management, with potential applications in real-world pest control. The study underscores the potential of EO-based nano-emulsions as a safe, effective, and environmentally sound alternative to chemical insecticides.

High-energy emulsification of Allium sativum essential oil boosts insecticidal activity against Planococcus citri with no risk to honeybees - Antonino Modafferi; Giulia Giunti; Alberto Urbaneja; Francesca Laudani; Ilaria Latella; Meritxell Pérez-Hedo; Michele Ricupero; Vincenzo Palmeri; Orlando Campolo (Journal of Pest Science, 2025)
The ecotoxicological consequences of synthetic pesticides have encouraged stakeholders to search for eco-friendly pest control tools, like essential oils (EOs). Nano-delivery systems (nanoparticles and nano-emulsions) seem ideal for developing EO-based biopesticides, although production processes should be standardized and implemented. In this study, nano-emulsions loaded with a high amount of Allium sativum L. EO (15%) were developed using different mixed bottom-up/top-down processes. Garlic EO was chemically analyzed by gas chromatography-mass spectrometry (GC-MS) and formulations were physically characterized using Dynamic Light Scattering (DLS) apparatus. The insecticidal activity against Planococcus citri Risso (Hemiptera: Pseudococcidae) and selectivity toward Apis mellifera L. (Hymenoptera: Apidae) worker bees was evaluated. Garlic EO was mainly composed of sulphur components (96.3%), with diallyl disulphide and diallyl trisulphide as the most abundant compounds (37.26% and 28.15%, respectively). Top-down processes could produce stable nano-emulsions with droplet size in the nanometric range (< 200nm) and good polydispersity index (PDI < 0.2). In contrast, the bottom-up emulsion was unstable, and its droplet size was around 500nm after 24 hours. High-energy emulsification processes significantly increased the residual toxicity of garlic EO against 3rd instar P. citri nymphs, whereas the developed formulations were harmless to A. mellifera workers in topical application. This study confirmed that the production process significantly affected the physical properties and efficacy against target pests. The lack of adverse impact on honeybees denotated the potential of these formulations as bioinsecticides in organic and/or IPM programs, although further extended ecotoxicological studies are necessary.

Ecological costs of botanical nano-insecticides - Antonino Modafferi; Giulia Giunti; Giovanni Benelli; Orlando Campolo (Current Opinion in Environmental Science & Health, 2024)